Cognitive beamforming for secondary spectrum access - Cai, Shengming (2015)
It has been widely accepted that cognitive radio can substantially improve the spectrum utilization compared with traditional spectrum allocation strategies. Cognitive radio technology enables secondary users to coexist with primary users opportunistically or concurrently. In the latter scenario, the primary user allows the secondary user to access its licensed spectrum, as long as the quality of service (QoS) of the primary transmission is guaranteed. Beamforming is a practical way to achieve this goal by utilizing multiple antennas to limit the interference at the primary receiver (PR) to a tolerable level. With transmit beamforming and receive beamforming, a multi-antenna secondary transmitter (ST) with the knowledge of cross channel state information (CSI) can project signals to appropriate directions such that no harmful interference is received at PR, while the secondary receiver (SR) can separate and recover the intended signals reliably. Perfect or imperfect knowledge of cross CSI at ST results in different interference conditions as well as different transmit strategies. The interference received at PR in the perfect cross CSI case is controllable, and hence ST can precisely determine the transmit beamforming directions to gain the maximum benefit under the primary interference constraint. However, such a strategy is not always suitable in the imperfect cross CSI case, due to the uncertainty of CSI error directions and amplitudes. In this case, ST needs to ensure that the interference constraint would not be violated even with the worst CSI error.